LINGKUNGAN PENDIDIKAN ISLAM DAN KONTRIBUSINYA DALAM PENDIDIKAN - Fajri Chairawati (Jurnal Ilmiah Pendidikan Anak (JIPA), 2021)
This paper examines three kinds of educational environments that play a role and also influence the success or failure of education for children. The three types of educational environment are the family environment (informal), the school environment (formal), and the community environment (non formal). The family environment is the first and foremost environment that children get. Father and mother as parents are natural educators who provide education to their children both before and after the child is born. Meanwhile, the school environment is an environment where at a certain age a child will definitely be given up by his parents to receive education in a more formal form. The educators are called teachers as professional educators. The last one is the community environment where of course the child is also a social being who interacts with the social environment around him. Educators in society here are all elements that exist in society. From the three types of environment, the results show that between one environment and another, they complement each other and have a role and contribution in providing education to children. Good and bad, the success or failure of the education obtained by children is very dependent on what they get from the three educational environments. Keywords: Islamic Education Environment, Contribution